2021
DOI: 10.1101/2021.02.16.431334
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transposable Elements Shape Stemness in Normal and Leukemic Hematopoiesis

Abstract: Despite most acute myeloid leukemia (AML) patients achieving complete remission after induction chemotherapy, two thirds of patients will relapse with fatal disease within 5 years. AML is organized as a cellular hierarchy sustained by leukemia stem cells (LSC) at the apex, with LSC properties directly linked to tumor progression, therapy failure and disease relapse 1-5. Despite the central role of LSC in poor patient outcomes, little is known of the genetic determinants of their stemness properties 6-8. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 110 publications
(235 reference statements)
0
2
0
Order By: Relevance
“…AML is often associated with epigenetic alterations in DNA methylation and modification of histones. In a 2021 preprint, Nadorp et al revealed that LSCs and mature leukemic cells display different chromatin accessibility profiles for diverse TE subfamilies ( Nadorp et al, 2021 preprint). Interestingly, TEs located in the accessible chromatin of LSCs act as docking sites for several oncogenic drivers of AML, including LYL1, a proto-oncogene of the TAL family ( Nadorp et al, 2021 ).…”
Section: The Role Of Tes In Hematological Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…AML is often associated with epigenetic alterations in DNA methylation and modification of histones. In a 2021 preprint, Nadorp et al revealed that LSCs and mature leukemic cells display different chromatin accessibility profiles for diverse TE subfamilies ( Nadorp et al, 2021 preprint). Interestingly, TEs located in the accessible chromatin of LSCs act as docking sites for several oncogenic drivers of AML, including LYL1, a proto-oncogene of the TAL family ( Nadorp et al, 2021 ).…”
Section: The Role Of Tes In Hematological Cancersmentioning
confidence: 99%
“…In a 2021 preprint, Nadorp et al revealed that LSCs and mature leukemic cells display different chromatin accessibility profiles for diverse TE subfamilies ( Nadorp et al, 2021 preprint). Interestingly, TEs located in the accessible chromatin of LSCs act as docking sites for several oncogenic drivers of AML, including LYL1, a proto-oncogene of the TAL family ( Nadorp et al, 2021 ). By contrast, a large proportion of the TE pool is repressed by methylation in AML ( Capone et al, 2018 ).…”
Section: The Role Of Tes In Hematological Cancersmentioning
confidence: 99%